Building Fit-For-Purpose Land Administration Systems: Guiding Principles :Guiding Principles - Enemark, Stig (2020)
This paper describes the key principles for building sustainable and FFP land administration systems especially in developing countries where often less the 10 per cent of the land and population is included in the formal systems. It is argued that building such FFP land administration systems is the only viable solution to solving the global security of tenure divide. The FFP approach is flexible and includes the adaptability to meet the actual and basic needs of society today and having the capability to be incrementally improved over time. This will be triggered in response to social and legal needs of economic development, investments and also financial opportunities that may emerge over the longer term. In this FFP approach, land rights can be secured for all in a timely and affordable way. The core elements of the FFP approach are laid down in joint FIG/WB declaration (FIG/WB, 2014) that includes the following statement.